Sex differences in immune protection in mice conferred by heterologous vaccines for pneumonic plague - Davies, Michael L.; Biryukov, Sergei S.; Rill, Nathaniel O.; Klimko, Christopher P.; Hunter, Melissa; Dankmeyer, Jennifer L.; Miller, Jeremy A.; Shoe, Jennifer L.; Mlynek, Kevin D.; Talyansky, Yuli; Toothman, Ronald G.; Qiu, Ju; et al. (Frontiers in Immunology, 2024)
Background Yersinia pestis is the etiological agent of plague, which can manifest as bubonic, septicemic, and/or pneumonic disease. Plague is a severe and rapidly progressing illness that can only be successfully treated with antibiotics initiated early after infection. There are no FDA-approved vaccines for plague, and some vaccine candidates may be less effective against pneumonic plague than bubonic plague. Y. pestis is not known to impact males and females differently in mechanisms of pathogenesis or severity of infection. However, one previous study reported sex-biased vaccine effectiveness after intranasal Y. pestis challenge. As part of developing a safe and effective vaccine, it is essential that potential sex differences are characterized. Methods In this study we evaluated novel vaccines in male and female BALB/c mice using a heterologous prime-boost approach and monitored survival, bacterial load in organs, and immunological correlates. Our vaccine strategy consisted of two subcutaneous immunizations, followed by challenge with aerosolized virulent nonencapsulated Y. pestis. Mice were immunized with a combination of live Y. pestis pgm- pPst-Δcaf1, live Y. pestis pgm- pPst-Δcaf1/ΔyopD, or recombinant F1-V (rF1-V) combined with adjuvants. Results The most effective vaccine regimen was initial priming with rF1-V, followed by boost with either of the live attenuated strains. However, this and other strategies were more protective in female mice. Males had higher bacterial burden and differing patterns of cytokine expression and serum antibody titers. Male mice did not demonstrate synergy between vaccination and antibiotic treatment as repeatedly observed in female mice. Conclusions This study provides new knowledge about heterologous vaccine strategies, sex differences in plague-vaccine efficacy, and the immunological factors that differ between male and female mice.